Effects of Broken Families in the Personal Development of the Students in BSED Values Major at Bestlink College of the Philippines: Towards Guidelines: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This survey research was conducted to determine the effects of broken families on the personal development of the BSED Values major at Bestlink College of the Philippines. Questions were formulated to guide the study. The study population consists of 1st year to 4th-year values major students. Through purposive sampling, 30 students were selected to participate in the study. The major instrument used for gathering data was a survey questionnaire. The data gathered were analyzed through the use of percentages and weighted mean. Based on the analysis, it was discovered that most respondents are afraid to open up to other family members.  They encountered major problems with their mental and emotional condition, performing low self-esteem, suicide and depression. Based on such findings, recommendations were made that local government should provide more seminars and orientations about having a happy family. School administrators should strengthen and increase the number of qualified counsellors in giving proper guidance and counselling students to increase self-confidence and result in better personal development. Through the process of this paper, the researcher can see the real problem that occurred in each situation of respondents. There is a need for attention and guidance for those facing this kind of problem. Family should be a source of unconditional love and a source for all of us to wither life's changes and challenges. Children can learn what it means to be a happily married woman or man, along with the qualities of a good father or mother. And, if the parents failed to be a parent and as a husband and wives, the children would suffer. In that way, the problem will occur. A broken family can negatively affect all domains of your child’s development, including the personal development of children.